ANALISIS PERSEPSI DAN MINAT GENERASI KEDUA KELUARGA PETERNAK AYAM BROILER TERHADAP USAHA PETERNAKAN AYAM BROILER DI KABUPATEN MAJALENGKA - Ulfa Indah Laela Rahmah; Lili Adam Yuliandri; Azzam Rousand Fikri (Fakultas Pertanian Universitas Majalengka, 2022)
ABSTRACT This study aims to determine and analyze the perceptions and interests of the second generation of broiler breeder families towards broiler chicken farming in Majalengka Regency, as well as analyze the factors that influence the perception and interest of broiler chicken business towards the second generation of broiler breeder families in Majalengka Regency. This research is a quantitative descriptive research, data collection using interviews with the census system. The variables observed in this study were income, environmental conditions, government attention, social status and parental support which were then analyzed using the Scale Range method and Multiple Linear Regression Analysis. The results showed that obtained from the perception of the second generation of broiler farming families towards broiler chicken farming in Majalengka Regency that it was categorized as